miR-375 Inhibits the Proliferation, Migration and Invasion of Esophageal Squamous Cell Carcinoma by Targeting XPR1 - Wu, Wenbin; Zhang, Yangmei; Li, Xiaowu; Wang, Xiang; Yuan, Yuan (Current Gene Therapy, 2021)
Objective: The purpose of this study was to explore the mechanism of the miR-375/XPR1 axis in esophageal squamous cell carcinoma (ESCC) and provide a new idea for targeted therapy of ESCC. Methods: Differentially expressed genes in GEO and TCGA databases were analyzed by bioinformatics. The expression levels of miR-375 and XPR1 mRNA were detected by qRT-PCR. Protein expression of XPR1 was detected by western blot. Bioinformatics analysis and dual luciferase assay were conducted to confirm the target relationship between miR-375 and XPR1. The viability, proliferation, migration and invasion of cells in each treatment group were detected by CCK-8, colony formation, wound healing and Transwell assays. Results: Significantly down-regulated miR-375 and remarkably up-regulated XPR1 were observed in ESCC tissue and cells. Overexpression of miR-375 inhibited proliferation, invasion and migration of ESCC cells, and greatly reduced the promoting effect of XPR1 overexpression on cell proliferation, migration and invasion. Dual luciferase assay confirmed that miR-375 targeted and inhibited XPR1 expression in ESCC. Conclusion: These results demonstrate the regulatory role of the miR-375/XPR1 axis in ESCC cells and provide a new potential target for the precise treatment of patients with ESCC.
Keywords: migration